A note on unique range sets of meromorphic functions with deficient values - Banerje, Abhijit; Majumder, Sujoy
With the help of the notion of weighted sharing of sets we deal with the problem of Unique Range Sets for meromorphic functions and obtain a result which improve some previous results.
Keywords: Meromorphic functions; Uniqueness; Weighted sharing